The Influence of Guerrilla Marketing on Buying Interests in Indonesian Fashion Local Brands - Karen Millennia Puspa Nugroho; Daniel Hermawan (Universitas Airlangga, 2022)
The modern age has had an impact on commercial sectors, particularly the fashion industry. There are already an increasing number of local brands that are in demand from the general public, particularly ladies. But the local fashion brand's marketing strategy is not wholly responsible for its success. The typical marketing strategy is now less effective due to technology innovation. Thus, a non-traditional strategy using digital marketing tools like web hunt can make it simpler for Indonesian fashion local products to be noticed and purchased by many people in various places. Therefore, the goal of this study is to analyse how guerrilla marketing has an impact on Indonesian consumers' shopping habits and local fashion brands. The quantitative approach combined with a descriptive analysis was the research methodology employed in this study. A survey of 103 respondents who fit the requirements for the data collecting process—product owners and potential customers of a regional fashion brand in Indonesia—was utilized to gather the information. The study's findings show that guerrilla marketing has an impact on Indonesian local fashion brands' consumer behaviour at the same time. However, in part, the emotional arousal factor has the greatest impact on consumers' purchasing decisions. Therefore, it may be said that guerrilla marketing has little effect on consumer behaviour.